Perceptions and Attitudes of College Teachers toward Inclusive Education in Punjab, Pakistan - Aftab, Muhammad Javed; Faisal Amjad,; Naz , Bushra (JIE, 2025)
This research aimed to explore the perceptions and attitudes of university teachers towards inclusive education in Punjab, Pakistan. To accomplish this, the researchers employed a quantitative research method, selecting 200 college teachers through simple random sampling. The researchers collected data by administering a self-developed questionnaire, which experts subsequently reviewed to ensure its validity, and measured reliability using Cronbach's alpha. The study's findings reveal a strong endorsement of inclusive education among teachers, who are aware of the benefits and show the desired confidence in adopting their teaching methods following the different learning needs. However, we identified the primary issue as the scarcity of resources, which could potentially impede the successful integration of practices. While demographic factors such as gender, designation, and area of posting had an impact on the opinions of the people, qualifications and experience did not turn out to be remarkably influential. These results illustrate a trend towards a supportive attitude towards inclusive education, evidenced through resource allocation, despite remaining challenges in finance for education. The study points to the significance of support systems and pinpoints professional development for the effectiveness of inclusive education